Peningkatan Kompetensi Pedagogik Guru PAI dalam Pembelajaran - Ismail Darimi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
Teachers are required to have superior competence in their field, pedagogical competence of teachers is one of the competencies required of every teacher in any field of education and, not least teachers PAI. Increased PAI Teachers Pedagogic Competence in Learning to be more focused and a special concern for Islamic educational institutions in particular and government in general. Teachers who could humanize the character and noble, noble character, and personality superior and dignified exist on teacher PAI, when teachers PAI can not increase the competence of pedagogical, it will affect the students receive knowledge transformation in the learning process, so that learning is considered failed and education became a taboo and is not important in view of the public. Human resource development, especially for teachers of Islamic education is a right answer to straighten out problems in education that has been ensnared education, in order to be repaired morals and manners of generation of people in accordance with the teachings of Islam that is almost swallowed by the times.